2011
DOI: 10.5897/ajb11.2351
|View full text |Cite
|
Sign up to set email alerts
|

Fish (Arius heudelotii Valenciennes, 1840) as bio-indicator of heavy metals in Douala Estuary of Cameroon

Abstract: This study assessed and monitored accumulation levels of heavy metals (Fe, Pb, Cu, Zn and Mn) in a prominent benthic mangrove fish species (Arius heudelotii Valenciennes, 1840) from the Douala Estuary, Cameroon. Fish species selection was based on signs of deterioration in taste and texture. Sampled estuarine water and tissue parts (liver, gut, flesh, gills and bones) of the captured fish were analyzed using atomic absorption spectrophotometer. The results show that concentration of the heavy metals except Mn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The use of fertilizers, insecticides, herbicides and other chemicals by farmers and agro-establishments may be a threat to the environment especially the soil and water quality. Unfortunately, the legislation on farming practices and or waste disposal in Cameroon are hardly implemented (Fonge et al, 2011;Forton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The use of fertilizers, insecticides, herbicides and other chemicals by farmers and agro-establishments may be a threat to the environment especially the soil and water quality. Unfortunately, the legislation on farming practices and or waste disposal in Cameroon are hardly implemented (Fonge et al, 2011;Forton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…All heavy metals are potentially harmful to most organisms at some levels of exposure and absorption (Adedeji and Okocha, 2011). The ingestion of heavy metals by fish via food and water may affect not only the productivity and reproductive capabilities of such fish, but ultimately affect the health of man that depends on these organisms as a major source of protein (Fonge et al, 2011). Many ecotoxicological studies in Nigeria have focused on aquatic bodies within or around major cities with little emphasis on aquatic media in rural areas, which may also be impacted by heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies conducted in Cameroon on the effect of trace metals on these marine systems had focused on the Cameroon estuary in the Douala metropolitan area. For instance, the fish Arius heudelotii was identified as bioindicator of trace metal pollution in Douala and the concentration of trace metals in fish and water samples were noted to be higher than safety limits of the World Health Organization (Fonge et al 2011). Also, subsurface soils in the Bassa industrial zone Douala showed enrichments of trace metals (Asaah et al 2006).…”
Section: Introductionmentioning
confidence: 99%